Performan Produksi Kambing Saburai Jantan Pada Dua Wilayah Sumber Bibit di Kabupaten Tanggamus - Kusuma Adhianto; M. Dima Iqbal Hamdani; Sulastri Sulastri; Indah Listiana (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2016)
Saburai goat was crossing breed by grading up between male Boer and female Ettawah grade goat. This research was conducted to compare production performance of male Saburai goat at Gisting subdistrict and Sumberejo subdistrict as Saburai goat breeding source area. Survey method were used in this research by observation to 90 at Gisting subdistrict and 90 at Sumberejo subdistrict tails male Saburai goat as sample. The sample were choosed by purposive sampling method. Variables observed were birth weight (BW), weaning weight (WW), yearling weight (YW), average of preweaning daily gain (APreDG), average of postweaning daily gain (APostDG). The data was analyzed by t-student test. Result of research indicated that BW (3,42+0,28 kg), WW (16,22+3,77 kg), YW (36,56+4,85 kg), APreDG (140,00+0,04 g/tail/day), APostDG (70,00+0,02 g/tail/day) of Saburai goat at Gisting subdistrict was not different (P>0,05) with Saburai goat at Sumberejo subdistrict (BW 3,48+0,41 kg, WW 16,85+258 kg, YW 38,30+5,35 kg, APreDG 150,00+0,03 g/tail/day, APostDG 80,00+0,02 g/tail/day). Keywords: performance production, Saburai male goat, Tanggamus